Peningkatkan Kemampuan Kognitif Melalui Media Main Numerik Pada Anak Usia 3-4 Tahun - Fidesrinur Fidesrinur; Nila Fitria; Zahrina Amelia (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
This study aims to improve the cognitive abilities of children aged 3-4 years using numerical play media. This research method, which is an experiment involving 10 parents, is expected to be an alternative for children's habituation to direct experience involving all of the child's senses. Action research will be conducted in the Kemmis & Taggart model. Each cycle consists of four stages, namely: planning, implementing actions, observing, and reflecting. The research subjects were children aged 3-4 years. Data collection techniques were carried out through observation, interview, documentation study. The data collected were analyzed descriptively qualitatively and quantitatively. The results showed that the cognitive improvement in the first cycle was 75% in the good category and the second cycle reached 86.8% in the very good category. Based on the analysis in cycle I and cycle II, the researcher can conclude that the use of Numerical Main Media can improve the cognitive abilities of children aged 3-4 years. Keywords: Cognitive ability, early childhood, numeric playing media.